Deep sedation Vs. general anesthesia in 232 patients undergoing percutaneous mitral valve repair using the MitraClip® system. Issue 7 (23rd January 2017) - Horn, Patrick; Hellhammer, Katharina; Minier, Michael; Stenzel, Monika A.; Veulemans, Verena; Rassaf, Tienush; Luedike, Peter; Pohl, Julia; Balzer, Jan; Zeus, Tobias; Kelm, Malte; Westenfeld, Ralf
Abstract : Objectives: To investigate in a series of 232 patients whether the MitraClip ® procedure can be performed safely using deep sedation (DS) without general anesthesia (GA). Background: Transcatheter mitral valve repair using the MitraClip ® system is a safe and effective therapy for severe mitral regurgitation (MR) in patients who are at high operative risk or are unsuitable for surgery. For these patients, avoidance of GA might be beneficial. Methods: Between 2011 and 2015, we performed 232 MitraClip ® procedures for the treatment of severe MR. Of those, 76 procedures were performed using GA, while the remaining 156 procedures were performed using DS. Results: Age, logistic EuroScore, severity of MR, left and right ventricular function, and renal function did not differ between the groups. The primary combined safety endpoint, which was defined as the occurrence of major adverse cardiac and cerebrovascular events, conversion to surgery, major vascular complications or pneumonia, did not differ between MitraClip ® procedures performed using GA and MitraClip ® procedures performed using DS. Intraprocedural conversion to GA was required in 2% of the patients in the DS group. There were no differences in procedural success or clinical outcome between the groups at the 3‐month follow‐up. Preparation time in the catheterization laboratory and intensive care unit (ICU) stay were shorter in the DS group compared to the GA group. Conclusion: The MitraClip ® implantation performed using DS is as safe and effective as MitraClip ® implantation performed using GA. © 2017 Wiley Periodicals, Inc.